A Literature Review of Corporate Governance Reform in the UK: 1985 and Today - Kaur, Gurleen (2013)
The thesis explores the corporate governance system of the UK. This is achieved by providing answers to the main research questions. First, what exactly is corporate governance and why is it a critical issue in the UK? Second, how did the corporate governance issue arise in the UK, and therefore rose after the passage of the Cadbury Report? Third, what formulate the good governance principles in the UK, and how have they changed with the passage of various committees as well ad-hoc reports? The study is a literature review involving critical analysis and documents evidence relating to each of the answer. The findings are consistent with the view that corporate governance system within the UK has reformed, making the system better. In the end, the thesis documents evidence by using annual reports of pre-Cadbury and post Cadbury period of a multinational UK based corporation.